2013
DOI: 10.1186/1755-1536-6-18
|View full text |Cite
|
Sign up to set email alerts
|

The role of mouse strain differences in the susceptibility to fibrosis: a systematic review

Abstract: In humans, a number of genetic factors have been linked to the development of fibrosis in a variety of different organs. Seeking a wider understanding of this observation in man is ethically important. There is mounting evidence suggesting that inbred mouse strains with different genetic backgrounds demonstrate variable susceptibility to a fibrotic injury. We performed a systematic review of the literature describing strain and organ specific response to injury in order to determine whether genetic susceptibil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
114
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(117 citation statements)
references
References 90 publications
1
114
2
Order By: Relevance
“…Although Clarke et al [34] recently suggested that the collagen fibre structure and the mechanical properties of infarcted tissue could vary between studies employing the same animal model, the reason behind this variation is not very well understood. Nevertheless, the discrepancy between our results and that of Fomovsky and Holmes [20] could potentially be attributed to the difference in animal strain [35,36]. It could also be due to the variation in the amount of isolated muscle fibres especially when considering the difficulty of precisely controlling the size of the infarct in the samples as we demonstrated in this study.…”
Section: Mechanical Properties Of Infarctscontrasting
confidence: 49%
“…Although Clarke et al [34] recently suggested that the collagen fibre structure and the mechanical properties of infarcted tissue could vary between studies employing the same animal model, the reason behind this variation is not very well understood. Nevertheless, the discrepancy between our results and that of Fomovsky and Holmes [20] could potentially be attributed to the difference in animal strain [35,36]. It could also be due to the variation in the amount of isolated muscle fibres especially when considering the difficulty of precisely controlling the size of the infarct in the samples as we demonstrated in this study.…”
Section: Mechanical Properties Of Infarctscontrasting
confidence: 49%
“…Although various studies have shown myocardial fibrosis and apoptosis in different models of diabetic cardiomyopathy, other investigators have observed the absence of fibrosis and apoptosis (32). Variability in the degree of myocardial fibrosis and apoptosis in diabetic rodent models has been explained by differences in animal species (2), differences in mouse strains (41), variable levels of hyperglycemia (39), differences in compensatory upregulations of metalloproteinases (43), and differences in the effects of STZ (7), the last of which may cause nonspecific toxicity besides pancreatic injury and includes tissue apoptosis. Importantly, in our study, all cardiac changes in apoE Ϫ/Ϫ mice were prevented by insulin, supporting that hyperglycemia, rather than nonspecific STZ toxicity, was the responsible factor.…”
Section: Discussionmentioning
confidence: 99%
“…Adoptive transfer of cells to mouse with different H-2 antigen is possibly immunogenic. The mice strain usually used to study chronic kidney damage is C57BL6 based on its susceptibility to renal fibrosis [34]. On the other hand, to achieve a stable φ-NGAL transduction, we used the commercial cell line RAW264.7.…”
Section: Discussionmentioning
confidence: 99%